Prevalence and Evaluation of Self-Medication Practices in Butwal, Rupandehi, Nepal - Chaudhary, Mukesh Kumar; Gaire, Krishna Kala; Gupta, Pooja; Banjade, Sushmita (Indian Journal of Pharmacy Practice)
Introduction: Use of medicine without the prescription of doctors is called self-medication, which is widespread in various countries. This becomes one of the emerging problems. The aim of study was to know the status of this type of practice in Butwal. Materials and Methods: Study was conducted in community pharmacies of Butwal. Minimum sample size of the study was found to be 379. From previous study, a questionnaire form was prepared and pilot study was done. Then data was collected of that patient practicing self-medication. Demographic information of patients, and information about drugs used self-medication and associated factors were recorded. Results: Total 811 patient were involving in study among which 385 (47.47%) were involve in self-medication practice. Among 385, 17 patients deny to response. The chief indications for this type of practice were headache, fever, and other pain (21.74%) followed by digestive disorder (17.66%) and hypertension (15.49%). Regular use, money saving and minor illness were foremost cause for self-medication. Anti-hypertensive (15.22%), Anti-gastritis (13.04%) and analgesic like Paracetamol (11.14%) were commonly used drugs. Previous prescription, previous experienced of use were the source of medication. Participants experienced very less side effects, male participants were more (51.35%) than female and majority of participants were from school level and from age group 15-30. Conclusion: Thus, the self-medication practice is common in Butwal. Public should be made aware about the negative consequences of this type of medication practice.
Keywords: Hypertension; Prescription; Questionnaire; Self-medication